The importance of calibration in policy mixes: Environmental policy integration in the implementation of the European Union's Common Agricultural Policy in Germany (2014–2022) - Pascal Grohmann; Peter H. Feindt (Environmental Policy and Governance, 2023)
Environmental policy integration (EPI), that is, the incorporation of environmental concerns in non-environmental policy areas, has been widely adopted in public policies. However, EPI research has found much discrepancy between environmental objectives and actual implementation. This paper argues that analyzing EPI in the context of policy mixes with multiple objectives, multiple instruments and their calibrations helps to better understand unavoidable tensions and limitations. We develop a framework to assess EPI at these three levels of policy output, synthesizing the EPI and policy mix literatures. We further distinguish four analytical dimensions to assess calibrations: stringency, specificity, flexibility, and temporality. A case study of the national implementation of the European Union's Common Agricultural Policy (CAP) in Germany 2014–2022 is used to elaborate the conceptual argument. The CAP has saliently incorporated environmental objectives, while implementation, including the calibrations of most instruments within predetermined corridors, is left to member states. A systematic meta-review of 142 texts evaluating policy instruments and calibrations in the CAP 2014–2022, focusing on Germany, found that several CAP instruments link most farm income support to pro-environmental behavior. These instruments could potentially have high environmental effectiveness and efficiency. But actual policy calibrations delivered weak EPI due to low stringency and specificity, while high flexibility and temporal accommodation of farmers' needs might support EPI by increasing acceptance. Weak EPI resulted from instrument calibrations in the face of unavoidable trade-offs between competing objectives. Our results demonstrate that calibrations can significantly affect the strength of EPI adoption, and the priorities within policy mixes more generally.
Keywords: 330; CAP; policy calibration; policy design; policy implementation; policy instruments; policy mixes